Multifunctional structural supercapacitor based on graphene and geopolymer. (10th January 2017) - Xu, Jiaming; Zhang, Dong
Abstract: A novel multifunctional structural supercapacitor based on graphene and geopolymer infused with 2 M KOH electrolyte was fabricated. Metakaolin-based geopolymers, which were first applied as structural separators in this paper, were prepared with metakaolin and different moduli of alkaline activator solution. The widespread pores in geopolymer matrix provide enough channels for ion storage and motion. The effects of alkaline activator solution modulus and curing age on the electrochemical properties were analyzed. The results revealed the ideal capacitive behavior of structural supercapacitor. The samples with modulus of 2.0 exhibited the highest specific capacitance of 36.5 F g −1 at curing age of 28 days. A possible mechanism was proposed to explain the factors that influence the specific capacitance of geopolymer-based structural supercapacitor. The result of multifuncitonality analysis showed that samples with modulus of 1.6 exhibited the best level of multifunctionality, with compressive strength of 33.85 MPa and specific capacitance of 33.4 F g −1 at curing age of 28 days. It achieved a balance between mechanical property and electrochemical performance.